2004
DOI: 10.4049/jimmunol.172.8.4733
|View full text |Cite
|
Sign up to set email alerts
|

A Toll-Like Receptor 2 Ligand Stimulates Th2 Responses In Vivo, via Induction of Extracellular Signal-Regulated Kinase Mitogen-Activated Protein Kinase and c-Fos in Dendritic Cells

Abstract: The adaptive immune system can generate distinct classes of responses, but the mechanisms that determine this are poorly understood. In this study, we demonstrate that different Toll-like receptor (TLR) ligands induce distinct dendritic cell (DC) activation and immune responses in vivo. Thus, Escherichia coli LPS (TLR-4 stimulus), activates DCs to produce abundant IL-12(p70), but little IL-10, and stimulates Th1 and Tc1 responses. In contrast, Pam-3-cys (TLR-2 stimulus) elicits less IL-12(p70), but abundant IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

58
394
8
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 415 publications
(462 citation statements)
references
References 78 publications
58
394
8
2
Order By: Relevance
“…The differences in results, therefore, likely reflect cellular differences in the usage of cFos/AP-1 and/or differences in the stimulation of cFos/AP-1 (single vs. dual stimulation). Consistent with this hypothesis, cFos appears to have no negative effects on IL-6 production by TLR-stimulated DC from cFos -/-mice [44]. Our data indicate that the role of cFos in B cell cytokine production may be more complex than previously thought, and worthy of further investigation.…”
Section: Discussionsupporting
confidence: 84%
“…The differences in results, therefore, likely reflect cellular differences in the usage of cFos/AP-1 and/or differences in the stimulation of cFos/AP-1 (single vs. dual stimulation). Consistent with this hypothesis, cFos appears to have no negative effects on IL-6 production by TLR-stimulated DC from cFos -/-mice [44]. Our data indicate that the role of cFos in B cell cytokine production may be more complex than previously thought, and worthy of further investigation.…”
Section: Discussionsupporting
confidence: 84%
“…inhibit early IL-4 production by responding CD4 T cells and thus inhibit Th2 cell development. Our data indicating that TLR 2 ligands profoundly inhibit Th2 cell development are contradictory to those findings that have suggested the role of TLR2 ligands in the induction of Th2 responses (20,(33)(34)(35)(36)(37)(38). Nevertheless, there is a large body of published data that is consistent with our findings showing that TLR2 ligands, including Pam 3 Cys, either promote Th1 responses or inhibit Th2 responses (39 -47).…”
Section: Discussioncontrasting
confidence: 68%
“…This is intriguing because there are reports that S- (2,3- 4 -OH,trihydrochloride (Pam 3 Cys), another TLR2 ligand, favors Th2 cell differentiation perhaps by enhancing production of IL-10 by DCs (20). To examine this issue, we stimulated DCs with Pam 3 Cys and cocultured them with OT-II Th cells in the presence or absence of a blocking anti-IL10R Ab.…”
Section: Tlr Agonists Not Cytokines Activate Dcs To Suppress Early mentioning
confidence: 99%
“…There is a growing body of evidence suggesting that bacterial components with immune adjuvant activity, including CpG DNA [13], Nme PorB [31] or Shigella porins [20], act via Toll-like receptors (TLRs) and can induce both a Th1-and a Th2-immune response [45,[68][69][70]. In addition, it has been recently shown that TLR2 mediates Th1 responses via direct stimulation of Th1 cells and via IL-12 production by APCs, and that TLR2-mediated INF-γ production is crucial for protective immunity against several infectious pathogens [71].…”
Section: Discussionmentioning
confidence: 99%